The mechanism of the nitrogen- and phosphorus-containing fire retardants action in polymers of various classes - Bogdanova, Valentina V.; Kobets, Olga I. (Journal of the Belarusian State University. Chemistry, 2023)
A generalisation of studies on the identification of the mechanism of fire-retarding action of nitrogen- and phosphoruscontaining flame retardants in synthetic carbochain (polyethylene, polypropylene), heterochain (polyurethane) and natural coking (wood, peat) polymers has been carried out. Synthetic ammonium metal phosphates with a wide range of physico-chemical and thermal properties were used as flame retardants. The mechanism of the fire retardant action of the synthesised products was determined from the results of a study of the physico-chemical, physico-mechanical properties and composition of the thermolysis products of polymer compositions with different levels of fire resistance. The content of inhibitory elements (nitrogen, phosphorus) in the initial polymer compositions was determined to achieve the standard level of fire resistance. A difference has been established between the factors that have a decisive influence on the cessation of combustion of carbochain, heterochain, and coking polymers. A conclusion is made about the mechanism of the synergistic action of nitrogen- and phosphorus-containing flame retardants, which consists in the participation of phosphorus in the formation of heat-insulating foam structures in the condensed phase and in the entry of volatile nitrogen-containing flame retardants’s into the gas phase.